Novel Antifungal Compounds Discovered in Medicines for Malaria Venture’s Malaria Box - Eric H. Jung (American Society for Microbiology, 2018)
ABSTRACT Similarities in fungal and animal cells make antifungal discovery efforts more difficult than those for other classes of antimicrobial drugs. Currently, there are only three major classes of antifungal drugs used for the treatment of systemic fungal diseases: polyenes, azoles, and echinocandins. Even in situations where the offending fungal organism is susceptible to the available drugs, treatment courses can be lengthy and unsatisfactory, since eradication of infection is often very difficult, especially in individuals with impaired immunity. Consequently, there is a need for new and more effective antifungal drugs. We have identified compounds with significant antifungal activity in the Malaria Box (Medicines for Malaria Ventures, Geneva, Switzerland) that have higher efficacy than some of the currently used antifungal drugs. Our best candidate, MMV665943 (IUPAC name 4-[6-[[2-(4-aminophenyl)-3H-benzimidazol-5-yl]methyl]-1H-benzimidazol-2-yl]aniline), here referred to as DM262, showed 16- to 32-fold-higher activity than fluconazole against Cryptococcus neoformans. There was also significant antifungal activity in other fungal species with known antifungal resistance, such as Lomentospora prolificans and Cryptococcus gattii. Antifungal activity was also observed against a common fungus, Candida albicans. These results are important because they offer a potentially new class of antifungal drugs and the repurposing of currently available therapeutics. IMPORTANCE Much like the recent increase in drug-resistant bacteria, there is a rise in antifungal-resistant strains of pathogenic fungi. There is a need for novel and more potent antifungal therapeutics. Consequently, we investigated a mixed library of drug-like and probe-like compounds with activity in Plasmodium spp. for activity against two common fungal pathogens, Cryptococcus neoformans and Candida albicans, along with two less common pathogenic species, Lomentospora prolificans and Cryptococcus gattii. We uncover a previously uncharacterized drug with higher broad-spectrum antifungal activity than some current treatments. Our findings may eventually lead to a compound added to the arsenal of antifungal therapeutics.